Pengaruh Konsentrasi Serbuk Daun Salam (Syzygium polyanthum) sebagai Repellent Kecoa (Periplaneta americana) - Nurul Hiznah; Indah Werdiningsih; Yamtana Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Cockroaches are vectors that can transform some pathogenic microorganisms that causing di-seases in humans. The use of synthetic chemical insecticides for vector control has proven ef-fective, but they have negative impact for human health and the environment. One alternative for environmentally friendly insecticides is Salam (Syzygium polyanthum) leaves that contain essen-tial oils (citral and eugenol), flavonoids, and tannins. The active ingredients are decomposable and also safe for health. This study was aimed to knowing the most effective Salam leaf powder weight as repellent for cockroach (Periplaneta americana). The study was a quasi experiment with post test only with control group design and was conducted in May-June 2018. The number of cockroaches used was 240, all with same size. The cockroaches were exposed to three di-fferent weight of Salam leaves powder, i.e. 7 grams, 8 grams and 9 grams, and control. The cockroaches were observed every 10 minutes in three times (30 minutes) every 3 hours in the duration of 9 hours. The results show that the 7 grams leaves poweder has protection power of 56,5%; the 8 grams has protection power of 78%; and the 9 grams has protection power of 81,5%, and the control is 30%. The most effective variation for repelling cockroaches is 9 grams.